ANTI- INFLAMMATORY AND ANTI- BACTERIAL ACTIVITY OF COPPER NANOPARTICLES SYNTHESIZED FROM MYRTUS COMMUNIS LEAVES EXTRACT - Al-Jubouri, A. K.; Al-Saadi, N. H.; Kadhim, M. A. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2022)
A variety of organisms, including plants and bacteria, fungi, seaweeds, and microalgae, are involved in the biological synthesis of nanoparticles. Copper nanoparticles (CuNPs) can be synthesized using plant extracts, which is considered to be one of the safest methods in green chemistry. Copper-NPs were synthesized from the leaves of M. communis, which were extracted with water. The first indication that CuNPs have been synthesized is the change in color of the solution from light yellow to dark brown. Several different techniques were used to characterize CuNPs. The Surface Plasmon Resonance (SPR) of the nanoparticles in the range of 300 to 700 nm was investigated using ultraviolet-visible absorption spectroscopy (UV-Vis), and the Fourier Transforming Infrared analysis (FT-IR) was used to identify functional groups in biomolecules that act as a reducing and capping agent for NPs. The X-ray diffraction (XRD) analysis of CuNPs revealed that they are crystalline. In this study, the size and surface properties of biosynthesized nanoparticles were determined using atomic force microscopy (AFM). Copper-NPs had an average size of 53.55 nm, according to the results. In this study, the antibacterial and anti-inflammatory activity of CuNPs and extract were investigated. The antibacterial activity of CuNPs and M. communis extract was evaluated against Gram-negative bacteria (Klebsiella pneumoniae and Pseudomonas aeruginosa) and Gram-positive bacteria (Staphylococcus aureus, and Lactobacillus salivarins). Zone inhibition of up to 25 mm was observed in Staphylococcus aureus when the extract concentration was 100000 µg/mL. At various concentrations, the anti-inflammatory activity of both the extract and the CuNPs was assessed in vitro using the assays (albumin denaturation assay, membrane stabilization assay, and proteinase inhibitory activity). According to the findings, CuNPs demonstrated a significant anti-inflammatory activity when compared to a standard drug.